Setting Up and Implementing ArcGIS to Work with Maps and Geospatial Data with Python for Teaching Geoinformation Systems in Higher Education - Karelkhan, Nursaule; Kadirbek, Aknur; Schmidt, Peter (International Journal of Emerging Technologies in Learning (iJET), 2023)
Geoinformation systems, as teaching tools in education, are closely linked to interdisciplinary and natural sciences. Currently, the application of geoinformation systems (GIS) in the educational process holds great potential for higher education. This paper presents a pedagogical system for teaching and learning a GIS course, along with a wide range of information sources that educators can choose from. The pedagogical system of introducing special GIS courses is divided into content, organizational and methodological structures. The theoretical and practical foundations of the introduction of special GIS courses are also considered. Additionally, the paper provides information about practical works setting up and implementing ArcGIS to work with maps and geospatial data with Python. The pedagogical system described in this paper was employed in the educational process of the L.N. Gumilyov Eurasian National University (Astana, Kazakhstan) and K. Zhubanov Aktobe Regional University (Aktobe, Kazakhstan). This experimental research examines how perceptions of geocapabilities evolved among 119 higher education students as they acquired technical skills in web mapping by investigating real-world issues with ArcGIS.